2018
DOI: 10.1172/jci99081
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligonucleotides extend survival and reverse decrement in muscle response in ALS models

Abstract: Mutations in superoxide dismutase 1 (SOD1) are responsible for 20% of familial ALS. Given the gain of toxic function in this dominantly inherited disease, lowering SOD1 mRNA and protein is predicted to provide therapeutic benefit. An early generation antisense oligonucleotide (ASO) targeting SOD1 was identified and tested in a phase I human clinical trial, based on modest protection in animal models of SOD1 ALS. Although the clinical trial provided encouraging safety data, the drug was not advanced because the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
131
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 191 publications
(154 citation statements)
references
References 44 publications
3
131
1
2
Order By: Relevance
“…Previous data suggest this limitation may be due to the drug delivery paradigm in these experiments. The current study used a single bolus injection of ASO in rodent models while previous studies that observed total target protein lowering in CSF after ASO treatment in nonhuman primate models were performed with multiple intrathecal ASO injections 10, 21. Additionally, both transgenic animal models used here express wild‐type forms of the target protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous data suggest this limitation may be due to the drug delivery paradigm in these experiments. The current study used a single bolus injection of ASO in rodent models while previous studies that observed total target protein lowering in CSF after ASO treatment in nonhuman primate models were performed with multiple intrathecal ASO injections 10, 21. Additionally, both transgenic animal models used here express wild‐type forms of the target protein.…”
Section: Discussionmentioning
confidence: 99%
“…ASOs that recruit RNase‐H to degrade target mRNA and an inactive, control ASO with no sequence specificity were provided by Ionis Pharmaceuticals 10, 21 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antisense oligonucleotides (ASOs) hybridize by Watson–Crick base pairing to mRNAs, leading to degradation by ribonuclease H, inhibition of translation, or altered splicing. Dominant disorders can be treated with allele‐specific ASOs that specifically target the mutant transcript, or with non–allele‐specific ASOs that reduce both mutant and wild‐type transcript . The application of ASO therapy to neurological disorders is receiving increasing attention, and the US Food and Drug Administration has recently approved treatment for spinal muscular atrophy that uses intrathecal administration of an ASO at 6‐month intervals .…”
mentioning
confidence: 99%
“…Dominant disorders can be treated with allele-specific ASOs that specifically target the mutant transcript, or with non-allele-specific ASOs that reduce both mutant and wild-type transcript. 12,13 The application of ASO therapy to neurological disorders is receiving increasing attention, [14][15][16] and the US Food and Drug Administration has recently approved treatment for spinal muscular atrophy that uses intrathecal administration of an ASO at 6-month intervals. 17 The goal of the current work was to evaluate ASO therapy for SCN8A encephalopathy.…”
mentioning
confidence: 99%